Peran Alumni Pesantren Gontor Dalam Upaya Pengembangan Diri Menuju Kemandirian Santripreneur (Studi Pada Forum Bisnis Ikatan Keluarga Pondok Modern Darussalam Gontor) - Ahmad Lukman Fahri Rahman; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study presents the importance of the role of alumni in self-development efforts towards the independence of santripreneur. Even though extensive studies on the role of Pesantren alumni have been discussed, few discussions on the areas of self-development efforts towar ds santripreneurs have been paid. For this reason, this study aims to explore the role of alumni of the Gontor Islamic boarding school in an effort to develop themselves towards the independence of santripreneurs. This study employs a qualitative reseach design using a case study approach. Four participants the Gontor Islamic Bording School alumni who are members of the Business Forum (FORBIS) of the Gontor Modern Pondok Families Association (IKPM) who are involved in various business fields were recruited. The result shows that the role of alumni who involved in the FORBIS forum gives significant contributions to the independence of santripreneur that involves business development, business enterpreneurship, business finance, and business marketing. It also gives a significant contribution in the society, goverment, boarding school, and self-development. Keywords : Self-Development Towards Santripreneur Independence